“I didn't want them to see that I was spent”: educators' stress and emotional labor during the COVID-19 pandemic - Aaron Leo; Kristen C. Wilcox (Frontiers in Education, 2025)
Research has demonstrated the difficulties faced by educators during the COVID-19 pandemic. In these unprecedented conditions, educators were asked to manage their emotions in new and challenging ways, thus exacerbating their relatively high levels of stress levels and burnout. We contribute to research on the pandemic's impact on educators through a qualitative case study conducted with 88 educators working in six schools across New York State. In this paper, we explore these educators' experiences of emotional labor during the pandemic, drawing attention to the ways educators managed emotions along display rules that compelled them to mask signs of stress and maintain a positive attitude. Through the constant-comparison method of data analysis, we found collegial support to be a crucial resource which participants drew on to manage their emotions in this highly stressful context. These findings have important implications for educators and policymakers as stress is a major contributor to the workforce shortages many schools across the United States are currently experiencing.